2019
DOI: 10.1080/1331677x.2018.1553679
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of project management practices in the Czech social enterprises

Abstract: Project management is a well-established discipline among private companies, but not widely utilised in non-profit organisations. The purpose of this paper is to analyse the role of project management in social enterprises that combine these two organisational formsthe business and the charity-and contribute to the understanding of how social enterprises use project management practices to run their activities. A survey was conducted among Czech social enterprises listed in the Directory of social enterprises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Management of SMEs is defined as the process whereby the firm's entrepreneurs or owners rely on the current and past working experience derived from other working environments or places, skills, and exposures acquired to manage the firm (Mamabolo & Myres, 2020;Meyer et al, 2018). Project management practice has a significant impact on annual turnover and number of employees dynamics not only in private companies but in social enterprises as well (Kubíčková & Hodžić, 2019).…”
Section: Literature Review 21 Management Of Smesmentioning
confidence: 99%
“…Management of SMEs is defined as the process whereby the firm's entrepreneurs or owners rely on the current and past working experience derived from other working environments or places, skills, and exposures acquired to manage the firm (Mamabolo & Myres, 2020;Meyer et al, 2018). Project management practice has a significant impact on annual turnover and number of employees dynamics not only in private companies but in social enterprises as well (Kubíčková & Hodžić, 2019).…”
Section: Literature Review 21 Management Of Smesmentioning
confidence: 99%
“…It is unclear how many social enterprises use accepted project management practices as there is limited empirical evidence in the literature. A survey of project managers in 61 Czech social enterprises indicated that some project management practices were followed by almost half of the survey participants, but that 16% did not follow these practices at all (Kubíčková and Hodžić, 2019). Barriers to the adoption of project management practices were identified, with the survey responses indicating a lack of time (approximately 31%), lack of expertise (approximately 28%) and lack of money (25%).…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to the adoption of project management practices were identified, with the survey responses indicating a lack of time (approximately 31%), lack of expertise (approximately 28%) and lack of money (25%). In terms of specific project management practices, Kubíčková and Hodžić (2019) found that while 49% had allocated people to projects according to the specific needs of the project, only 33% had a project manager, and only 16% had an entire project team. Furthermore, they found that budgets, economic evaluations, and SWOT analysis were the most used tools.…”
Section: Resultsmentioning
confidence: 99%
“…It is always imperative to all the organizations to analyze its environment to identify the threats and opportunities and to frame the optimal and most appropriate strategies to achieve its long-term objectives and this process is not only important for manufacturing firms but also in the service sector (Volkova, 2015). Project management practice is an important tool in increasing higher business performance, particularly in social enterprises (Kubíčková and Hodžić, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%